Description of a new species of the genus Pseudepitettix Zheng (Orthoptera: Tetrigoidea: Cladonotinae) from China - Huang, Chao-Mei; Deng, Wei-An (Zootaxa, 2021)
Pseudepitettix convexa Deng, sp. nov. is described with detailed illustrations of external morphology. Comparison between new species and other species of the genus Pseudepitettix Zheng, 1995 is compiled into a table for identification. An updated key to species of the genus is given.